2014
DOI: 10.1186/1472-6882-14-321
|View full text |Cite
|
Sign up to set email alerts
|

Allicin prevents H2O2-induced apoptosis of HUVECs by inhibiting an oxidative stress pathway

Abstract: BackgroundAllicin, a primary ingredient of garlic, has been proposed to possess cardioprotective properties, which are commonly mediated by improved endothelial function.MethodsTo investigate the effect and mechanism of allicin on the apoptosis of human umbilical vein endothelial cells (HUVECs), we used Propidium iodide (PI) staining and Annexin V/ PI staining assays to establish a model of oxidative stress apoptosis induced by H2O2. MTT, RT-PCR and western-blot assays were used to detect the effects and mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 26 publications
4
37
0
1
Order By: Relevance
“…Chan et al (13) reported that allicin inhibited intracellular ROS production, rather than scavenging extracellular H 2 O 2 or free radicals in H9C2 cells. Conversely, allicin has been shown to exhibit the ability to indirectly scavenge oxygen free radicals in human umbilical vein endothelial cells (16), which is consistent with the findings of the present study. Therefore, the present study hypothesized that allicin may exert various biological abilities in order to protect against oxidative stress in various cell lines and tissues.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Chan et al (13) reported that allicin inhibited intracellular ROS production, rather than scavenging extracellular H 2 O 2 or free radicals in H9C2 cells. Conversely, allicin has been shown to exhibit the ability to indirectly scavenge oxygen free radicals in human umbilical vein endothelial cells (16), which is consistent with the findings of the present study. Therefore, the present study hypothesized that allicin may exert various biological abilities in order to protect against oxidative stress in various cell lines and tissues.…”
Section: Discussionsupporting
confidence: 93%
“…The glutathione (GSH)/glutathione disulfide (GSSG) ratio and malondialdehyde (MDA) concentrations were assessed using the GSH/GSSG Assay kit (Beyotime Institute of Biotechnology, Nantong, China) and the MDA Assay kit (Nanjing Jiancheng Biological Engineering Institute, Nanjing, China), according to the manufacturer's protocols. The superoxide dismutase (SOD) activity was measured using the SOD Assay kit (Nanjing Jiancheng Biological Engineering Institute), according to the manufacturer's protocols (16).…”
Section: Methodsmentioning
confidence: 99%
“…We found that ectopic expression of SFRP5 downregulated the expression of Bax, a well‐defined proapoptotic protein . Induction of Bax is involved in oxidative stress‐induced apoptosis in human umbilical vein endothelial cells . Most importantly, co‐expression of Bax restored apoptotic response in the presence of SFRP5.…”
Section: Discussionmentioning
confidence: 99%
“…1B). Based on these results, 500 µΜ was selected as the model dose (6) to induce cell death for subsequent experiments on apoptotic cell death.…”
Section: Mws-19 Inhibits 500 µM H 2 O 2 -Induced Death Of Huvecsmentioning
confidence: 99%
“…Reactive oxygen species (ROS), such as hydrogen peroxide (H 2 O 2 ) and superoxide (O 2-), lead to increases in vascular tone and participate in arterial contraction, and have a direct role in the pathogenesis of hypertension (3,4). The vascular endothelium, a thin layer of cells lining the inner surface of the vascular wall, produces and secretes various substances that preserve the integrity and functioning of the vascular system (5,6). Excessive levels of ROS in endothelial cells leads to impaired endothelial nitric oxide (NO) bioactivity (7,8).…”
Section: Introductionmentioning
confidence: 99%